Clear cell endometrial carcinoma: analysis of the results of a 20-year follow-up - K. P. Laktionov; G. M. Abdullayeva; O. A. Anurova; S. M. Gadzhiyeva (Опухоли женской репродуктивной системы, 2014)
The paper presents data on the clinical and morphological characteristics, clinical presentation, and treatment of clear cell carcinoma, as well as survival rates in patients with this condition. It shows an association of the expression of the intercellular adhesion molecules E-cadhedrin, α- and β-catenins, the molecule of Her-2/neu with the clinical and morphological pattern of the disease, which has been determined by an immunohisto- chemical assay.